CONCEPTION OF HEALTH, ILLNESS AND CARE OF CLIENTS WITH DIABETES MELLITUS - Valéria Lerch Lunardi; Wilson Danilo Lunardi Filho; Alexandre Oliveira Alves; Claúdia Sá Freire (Universidade Federal do Paraná, 2000)
This study was developed with the objective to understand the perceptions of carrying customers of diabetes on its process health-illness and the cares and the changes in the necessary style of life for a bigger production of health. Workshops with eleven carrying adult customers of diabetes had been carried through, approaching subjects related to the care and the factors related to the illness, that can or not compromise the production of health and the quality of life. From the analysis of the data, it was evidenced that the customers who consider health as an excellent state of welfare carries through well-taken care of necessary to reach it, while that the ones that recognize health as a disposal to fulfill tasks, are felt limited front to the illness and in conflict more; although they recognize that the accomplishment of cares provides the metabolic control, they consider that it implies disciplines and abdication of pleasures; they present one better conviviality with the illness, when they do not identify any complications in itself; they relate to fear front to the possible progression of the illness, what they consider as plus a stimulated to adhere to the cares. The biggest identified difficulty mentions the changes of habits and the adhesion to it to the treatment, what it seems to be brightened up by the acceptance and understanding of the mórbido process.